Strong Electronic and Magnetic Coupling in M4 (M = Ni, Cu) Clusters via Direct Orbital Interactions between Low-Coordinate Metal Centers - Chakarawet, Khetpakorn; Atanasov, Mihail; Marbey, Jonathan; Bunting, Philip C; Neese, Frank; Hill, Stephen; Long, Jeffrey R (Journal of the American Chemical Society, 2020)
We present an extensive study of tetranuclear transition-metal cluster compounds M4(NPtBu3)4 and [M4(NPtBu3)4][B(C6F5)4] (M = Ni, Cu; tBu = tert-butyl), which feature low-coordinate metal centers and direct metal-metal orbital overlap. X-ray diffraction, electrochemical, magnetic, spectroscopic, and computational analysis elucidate the nature of the bonding interactions in these clusters and the impact of these interactions on the electronic and magnetic properties. Direct orbital overlap results in strongly coupled, large-spin ground states in the [Ni4(NPtBu3)4]+/0 clusters and fully delocalized, spin-correlated electrons. Correlated electronic structure calculations confirm the presence of ferromagnetic ground states that arise from direct exchange between magnetic orbitals, and, in the case of the neutral cluster, itinerant electron magnetism similar to that in metallic ferromagnets. The cationic nickel cluster also possesses large magnetic anisotropy exemplified by a large, positive axial zero-field splitting parameter of D = +7.95 or +9.2 cm-1, as determined by magnetometry or electron paramagnetic resonance spectroscopy, respectively. The [Ni4(NPtBu3)4]+ cluster is also the first molecule with easy-plane magnetic anisotropy to exhibit zero-field slow magnetic relaxation, and under a small applied field, it exhibits relaxation exclusively through an Orbach mechanism with a spin relaxation barrier of 16 cm-1. The S = 1/2 complex [Cu4(NPtBu3)4]+ exhibits slow magnetic relaxation via a Raman process on the millisecond time scale, supporting the presence of slow relaxation via an Orbach process in the nickel analogue. Overall, this work highlights the unique electronic and magnetic properties that can be realized in metal clusters featuring direct metal-metal orbital interactions between low-coordinate metal centers.We present an extensive study of tetranuclear transition-metal cluster compounds M4(NPtBu3)4 and [M4(NPtBu3)4][B(C6F5)4] (M = Ni, Cu; tBu = tert-butyl), which feature low-coordinate metal centers and direct metal-metal orbital overlap. X-ray diffraction, electrochemical, magnetic, spectroscopic, and computational analysis elucidate the nature of the bonding interactions in these clusters and the impact of these interactions on the electronic and magnetic properties. Direct orbital overlap results in strongly coupled, large-spin ground states in the [Ni4(NPtBu3)4]+/0 clusters and fully delocalized, spin-correlated electrons. Correlated electronic structure calculations confirm the presence of ferromagnetic ground states that arise from direct exchange between magnetic orbitals, and, in the case of the neutral cluster, itinerant electron magnetism similar to that in metallic ferromagnets. The cationic nickel cluster also possesses large magnetic anisotropy exemplified by a large, positive axial zero-field splitting parameter of D = +7.95 or +9.2 cm-1, as determined by magnetometry or electron paramagnetic resonance spectroscopy, respectively. The [Ni4(NPtBu3)4]+ cluster is also the first molecule with easy-plane magnetic anisotropy to exhibit zero-field slow magnetic relaxation, and under a small applied field, it exhibits relaxation exclusively through an Orbach mechanism with a spin relaxation barrier of 16 cm-1. The S = 1/2 complex [Cu4(NPtBu3)4]+ exhibits slow magnetic relaxation via a Raman process on the millisecond time scale, supporting the presence of slow relaxation via an Orbach process in the nickel analogue. Overall, this work highlights the unique electronic and magnetic properties that can be realized in metal clusters featuring direct metal-metal orbital interactions between low-coordinate metal centers.